A Qualitative Study Exploring Management of Food Intake in the United Kingdom During the Coronavirus Pandemic - Randall, Tennessee; Mellor, Chloe; Wilkinson, Laura L. (Frontiers in Psychology, 2022)
The coronavirus pandemic has impacted dietary quality through increased emotional eating and extended time spent at home, as well as instances of panic buying due to uncertainty over food availability. We recruited an opportunistic sample of 40 adults living in the United Kingdom (Female = 25; Mean age = 41.9 years) (SD = 14.4) without any prior history of eating disorders. Semi-structured interviews were conducted in June 2020 and focused on the impacts of the COVID-19 lockdown on eating habits and experiences of panic buying. The data were transcribed and organized using the softwares Otter and Quirkos, respectively. Reflexive thematic analysis identified positive and negative changes to eating habits. Overall, themes highlighted that effective organization was vital to manage food purchases and consumption due to a reduced shopping frequency. However, overconsumption frequently occurred due to boredom and ease of accessing energy dense foods, which had negative implications for weight and body image. After indulging, participants attempted to revert to prior eating habits and adhere to a nutritious diet. Many also expressed the importance of having enough food to feed families, which was often reported as a reason for buying extra supplies. Understanding the long-term impacts of changes to eating habits that account for the novel coronavirus context is required to preserve health and prevent unintended changes to weight.